Prudence Accounting, Financial Distress, and Foreign Operations on Tax Avoidance: Leverage’s Moderating Role - Raainaa, Nural Achmad; Andriani, Arifah Fibri (Universitas Negeri Semarang, 2025)
Purpose : The study investigates the effect of prudence accounting, financial distress, and foreign operations on tax avoidance, while also examining the moderating role of leverage in these relationships. The research addresses inconsistencies in prior studies regarding the influence of these factors and highlights their relevance in Indonesia’s financial sector, which is highly regulated and susceptible to aggressive tax strategies. Method : Using secondary data from audited financial statements of financial sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023, this study employs panel data regression analysis. The fixed effect model was chosen as the best fit after Chow and Hausman tests. Findings : The results reveal that prudence accounting and financial distress positively and significantly affect tax avoidance, while foreign operations show no significant impact. Furthermore, leverage weakens the positive relationship between both prudence accounting and financial distress with tax avoidance, but does not moderate the relationship between foreign operations and tax avoidance. Novelty : The study offers a comprehensive framework by integrating prudence accounting, financial distress, and foreign operations with leverage as a moderating variable, providing empirical evidence on how these factors interact in shaping tax avoidance strategies in the regulated Indonesian financial sector.